Effectiveness of Helicopters in Fighting Forest Fires in Türkiye: A Data Envelopment Analysis Approach - Melih Yıldız; Ozan Öztürk; Tuğba Akbıyık (Fire)
This study aims to evaluate the effectiveness of helicopters in fighting forest fires in Türkiye. The increasing frequency and severity of forest fires, especially with climate change, require more effective aerial response methods. Helicopters play a critical role due to their operational advantages, such as maneuverability, rapid access, and water-carrying capacity. In this study, the types of helicopters used in Türkiye are analyzed, and their operational efficiency is evaluated using Data Envelopment Analysis (DEA). The results reveal that certain models show high efficiency, but some helicopters have room for improvement in terms of fuel consumption and technical performance. A balanced use of both Bambi Bucket and internal water tank systems in fighting forest fires in Türkiye and investing in domestic production is recommended.